Validation of a single liquid chromatography‐tandem mass spectrometry approach for oxytetracycline determination in bull plasma, seminal plasma and urine. Issue 7 (4th March 2022) - Bardhi, Anisa; Gazzotti, Teresa; Pagliuca, Giampiero; Mari, Gaetano; Barbarossa, Andrea
Abstract: Oxytetracycline is a broad‐spectrum antibiotic, which inhibits protein synthesis and is generally used for the treatment of pneumonia, shipping fever, leptospirosis and wound infections in cattle and swine. The present work proposes a novel liquid chromatography–tandem mass spectrometry (LC–MS/MS) method for oxytetracycline quantification in bull plasma, seminal plasma and urine, requiring limited sample treatment before analysis. Extraction with trichloroacetic acid followed by dilution of the supernatant in mobile phase proved to be effective in all three matrices, allowing to rapidly process large batches of samples. Sharp and symmetrical peak shape was obtained using a BEH C18 reversed‐phase column in a chromatographic run of just 3.5 min. The mass spectrometer operated in positive electrospray ionization mode and monitored specific transitions for oxytetracycline (461.1 → 425.8) and the internal standard demeclocycline (465.0 → 447.6). The method was validated over concentration ranges suitable for field concentrations of oxytetracycline found in each matrix, showing good linearity during each day of testing ( R 2 always >0.99), as also confirmed by analysis of variance (ANOVA) and lack‐of‐fit tests. Excellent accuracy and precision were demonstrated by calculated bias always within ±15% and CV% below 10% at all quality control (QC) levels in the three matrices. Matrix effect and recovery were investigated for both analytes, which showed consistent and comparable behaviour in each matrix. To our knowledge, this is the first validated approach for mass spectrometric determination of oxytetracycline in seminal plasma and urine. The method was successfully applied to samples collected during a pharmacokinetic study in bulls, allowing to assess the oxytetracycline concentration–time profile in plasma, seminal plasma and urine.